On the beach [videorecording (DVD)] - Peck, Gregory, 1916-2003; Gardner, Ava, 1922-1990; Astaire, Fred; Perkins, Anthony, 1932-1992; Shute, Nevil, 1899-1960 (MGM Home Entertainment : DVD Video, 2000)
Radioactive fallout from a nuclear war has wiped out the entire northern hemisphere, with the exception of Australia. With fallout expected momentarily, the Australians review their lives, establish new relationships and prepare for their tragic demise.